Guanylate-binding protein 5-mediated autophagy can promote the clearance of intracellular F. nucleatum in dental pulp cells during pulpitis - Minchun Huang; Bo Yang; Xiaojun Yang; Jin Hou; Xinzhu Li (BMC Oral Health)
Abstract Background IFN-γ is crucial in induction of inducible cell-autonomous immunity, and IFN-γ signaling pathway is activated in pulpitis. Guanylate-binding proteins (GBPs) are a family of IFN-inducible GTPases and could utilize autophagy or pyroptosis to mitigate infection. GBP5 is abundantly expressed in inflamed pulp and human dental pulp cells (HDPCs). Therefore, we hypothesize that GBP5 in HDPCs exerts an immune-regulatory role in defending against bacterium infection. Methods Fusobacterium nucleatum (F. nucleatum) was used to infect HDPCs, and immunoblotting and qRT-PCR were used to detect pyroptosis and autophagy. Pharmacological or genetic approaches were used to enhance or knock down GBP5 expression in HDPCs. Blood agar plate counting and immunoblotting were used to observe bacteria clearance effect and activation of autophagy. Student’s t-test and one-way ANOVA were individually used for comparisons between two and multiple groups. Statistical significance was set at P < 0.05. Results Following F. nucleatum infection in HDPCs, the autophagy marker LC3B was significantly upregulated while the mRNA and protein expression levels of p62 were increased. IFN-γ priming significantly inhibited the intracellular survival of F. nucleatum and enhanced the autophagic activity of HDPCs. GBP5 overexpression significantly increased the efficiency of HDPCs in clearing intracellular F. nucleatum and activated autophagic flux in HDPCs, while downregulating GBP5 in HDPCs suppressed autophagic flux. Conclusion IFN-γ-mediated GBP5 overexpression in HDPCs during F. nucleatum infection exerts an anti-microbial function through autophagy activation.